HOW DOES GAMIFICATION INFLUENCE A CONSUMER'S PURCHASE INTENTION? STUDY IN SHOPEE INDONESIA - Vania Lesmana; Vita Briliana (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
The purpose of this study is to determine the effect of perceived value dimensions as predictors of game use intention and platform purchase intention. This study uses the dimensions of perceived value, namely utilitarian value, hedonic value, social value, and time/effort, to predict game use intention and platform purchase intention. This research data consists of answers to questionnaires distributed online. Game users on the Shopee Indonesia platform in Jakarta were selected as the object of this research. The researcher selected the samples for this study using purposive sampling of 301 respondent data with specific criteria. We used the PLS structural equation modeling (SEM) method and SPSS for this study. The results obtained in this study show that utilitarian value, hedonic value, social value, and time/effort have an influence on the game use intention variable. Utilitarian Value, Social Value, and Game Use Intention variables affect the Platform Purchase Intention variable, while the Hedonic Value and Time/Effort variables have no effect on Platform Purchase Intention. Game use intention does not play a role in mediating the influence of utilitarian value, hedonic value, social value, and time/effort on platform purchase intention.